Alternative sanctions and new legislation in the Republic of Serbia - Mrvić-Petrović Nataša (Temida)
The author is particularly emphasizing peculiarities of the provision on community service as a main penalty (which is foreseen together with the fine and the prison). This solution requires not only the profound regulations in the Law on the execution of the criminal sanctions, but also a careful creation of the by-laws. In the paper, particular attention is paid to the new solutions in the Law on the execution of the criminal sanctions, which aim is to enable the implementation of the community service and the conditional sentence with the protective surveillance. The author states that previous changes of the Criminal Procedure Code, which introduced the principle of opportunity in prosecuting, made a basis for taking victim’s interests related to the redress more into account while starting the prosecution. However, the possibility of using the redress as a basis for the elimination/diversion of the criminal procedure is still not used in an appropriate way in the practice.